2017
DOI: 10.1002/pon.4425
|View full text |Cite
|
Sign up to set email alerts
|

Dual role as a protective factor for burnout‐related depersonalization in oncologists

Abstract: Differences in burnout-related DP scores between dual- and single-role oncologists are consistent with a protective effect from a psychosocial orientation in oncologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 34 publications
(67 reference statements)
0
13
0
3
Order By: Relevance
“…A total of 2015 hits were retrieved. After deleting duplicates (N = 386), irrelevant papers (N = 580), and exclusions (N = 915), we found 17 studies eligible to be included in this scoping review as shown in Figure 1 (3,15,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46).…”
Section: Results Of the Database Searchmentioning
confidence: 99%
“…A total of 2015 hits were retrieved. After deleting duplicates (N = 386), irrelevant papers (N = 580), and exclusions (N = 915), we found 17 studies eligible to be included in this scoping review as shown in Figure 1 (3,15,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46).…”
Section: Results Of the Database Searchmentioning
confidence: 99%
“…Previous research offers mixed results regarding the relationship between influence at work and emotional exhaustion. While some authors conclude that there is a significant and negative relationship between these two variables (He et al , 2017), others find a significant and positive relationship (Knudsen et al , 2006). Others affirm that there is no relationship between them (Ito and Brotheridge, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Influence at work can be considered either a job demand or job resource. As a resource, it refers to freedom in decision-making to obtain other resources needed to complete the tasks correctly (He et al , 2017; Kowalski et al , 2010); as a job demand, decisional decentralization may increase the number of everyday decisions, culminating in emotional exhaustion (Knudsen et al , 2009). Accordingly, in public healthcare, professionals have limited decision-making autonomy due to highly standardized procedures, rules and policies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…11 Roles characterized by low perceived task significance and variety, [47][48][49] and high-effort/low reward are also associated with greater burnout. [50][51][52]…”
Section: Role Characteristicsmentioning
confidence: 99%